Ultrasound‐guided needle handling using a guidance positioning system in a phantom. (9th November 2013) - Tielens, L. K. P.; Damen, R. B. C. C.; Lerou, J. G. C.; Scheffer, G.‐J.; Bruhn, J.
Summary The SonixGPS™ needle guidance positioning system provides navigation assistance to facilitate needle handling during ultrasound‐guided procedures. Each of 20 inexperienced nurse anaesthetists performed 12 different ultrasound‐guided tasks in a porcine phantom. Using both in‐plane and out‐of‐plane approaches, they inserted a needle and made contact with metal rods at depths of 2, 4 and 6 cm. We compared their performances without and with navigation as paired observations. Using the out‐of‐plane approach, navigation yielded shorter execution times (26 s vs 14 s, respectively; p = 0.01) and fewer needle repositionings (8 vs 3, respectively; p = 0.001). Using the in‐plane approach, the needle was more visible with navigation assistance: 24% vs 52% of execution time, respectively (95% CI: 44%–12%; p = 0.0025). Better needle visibility was associated with shorter execution times and fewer needle repositionings. Combining ultrasound‐guided techniques with the needle guidance positioning system may reduce tissue manipulation, thus improving patient comfort and safety.